Identifying Leadership Styles that Influence Students’ Learning Environment - Abu Afifeh, Khaleel Ali Ibrahim (2015)
This study aimed to identify leadership styles that influence the students’ learning environment. Specifically, the study attempted to answer the following questions: 1. What is the socio-demographic profile of faculty/teachers in terms of their age, sex, educational qualifications and years of experience? 2. What leadership styles do leaders manifest that affects the learning environment? 3. What leadership styles do leaders possesses that influence a better learning atmosphere? 4. What leadership traits that a leader must possess to help in the development of a better learning atmosphere? This research employed a descriptive design using both quantitative and qualitative methods of data gathering. Purposive selection was used in conducting this study. The researcher included one hundred two (102) respondents who were volunteered by their respective leaders. Three public schools and two private schools were chosen as participants. Respondents were volunteered by their leaders were mostly male and young professionals. Majority of the respondents were on their mid to master degree level having eleven to fifteen years of experience. The research combined both qualitative and quantitative research methodologies. Data were collected using both open ended questions and self- made questionnaire. These data were analyzed using both statistical techniques and expert panels. The results of this study were based from six leadership traits and six leadership styles. Leadership traits were communicator and friendly, insightful perspective, self-confidence and self-assured, secured, persistence and determination, and dependable and trustworthy. Leadership styles were pacesetting, authoritative, coaching, coercive, democratic and transformational.